Blood-borne Viral Infections in Hemodialysis Units in Iraq: A Narrative Review of Prevalence and Contributing Factors (مجلة الرازي الطبية, 2025)
Hemodialysis (HD) patients are at heightened danger of acquiring blood-borne viral infections, particularly hepatitis B virus (HBV) and hepatitis C virus (HCV), due to repeated vascular access, immunosuppression, and frequent exposure to blood products and invasive procedures. This review studies the prevalence of HBV and HCV infection and its related risk factors among hemodialysis patients in Iraq. Several key factors influence its prevalence, including length of dialysis, blood transfusion records, inadequate infection control measures, and low vaccination coverage. Although the overall prevalence of HBV and HCV is low among the general Iraqi population, dialysis patients exhibit disproportionately high infection rates, underscoring the need for enhanced surveillance, targeted vaccination programs, and strict adherence to infection control protocols. This review aims to inform healthcare workers and policymakers about current epidemiological trends and recommend strategic interventions to reduce the transmission of HBV and HCV in dialysis centers in Iraq.